2005
DOI: 10.1029/2004jb003183
|View full text |Cite
|
Sign up to set email alerts
|

Controls on conduit magma flow dynamics during lava dome building eruptions

Abstract: [1] Lava dome eruptions commonly display fairly regular alternations between periods of high and low or no activity with timescales typically of weeks to years and sudden transitions between effusive and explosive activity. We develop a transient model of the magma flow in a volcanic conduit from an open-system magma chamber with continuous replenishment. The model incorporates gas exsolution, bubble growth, gas escape through the magma, and decompression-induced crystallization and considers variations in mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 46 publications
(126 reference statements)
5
160
0
Order By: Relevance
“…However, because the focus of this work is the development of a relatively simple model capable of fitting geophysical time series within a modest solution time, we do not attempt to incorporate all possible physical-chemical processes in an erupting magma and the model is significantly simplified relative to some models of conduit flow [e. g., Melnik and Sparks, 2005].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because the focus of this work is the development of a relatively simple model capable of fitting geophysical time series within a modest solution time, we do not attempt to incorporate all possible physical-chemical processes in an erupting magma and the model is significantly simplified relative to some models of conduit flow [e. g., Melnik and Sparks, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…While early work considered primarily the elastic compressibility of the host rock surrounding the chamber [Stasiuk et al, 1993], more recent work has suggested that the compressibility of the magma plays a dominant role due to the high compressibility of the exsolved gas phase [Huppert and Woods, 2002;Melnik and Sparks, 2005].…”
Section: Chamber Compressibility and Host Rock Rigiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Melnik and Sparks [2005] proposed a transient model of magma flow in an open volcanic conduit including gas exsolution and escape, bubble growth as well as crystallization effects. They show that the system can fluctuate between two stable states, one being characterized by a high flow rate of less viscous magma and the other by a low flow rate of more viscous magma.…”
Section: Effect Of Conduit Flow Versus Other Deformation Sourcesmentioning
confidence: 99%
“…Large fluctuations in discharge rate are correlated with fluctuations of various signals such as ground deformation, seismicity and gas emissions. For long-term cycles, (months to years), the mechanism invoked is pressure changes occurring within a magma reservoir [Melnik and Sparks, 2005]. In some volcanic areas such as Soufrière Hills, Mt.…”
Section: Introductionmentioning
confidence: 99%